INTEGRATING LOCAL WISDOM: INNOVATIVE ASSESSMENT INSTRUMENT OF CRITICAL THINKING SKILLS IN SCIENCE LEARNING - Dini, Naffa Afkarina Izzata; Kuswanto, Heru (Universitas Labuhanbatu, 2025)
Purpose- This research aims to develop a valid and reliable instrument for measuring students' critical thinking skills in learning integrated with local wisdom.Methodology- The research addresses the need for culturally relevant assessment tools that align with modern educational goals and promote the appreciation of local heritage. Employing the ADDIE development model, the study follows a systematic approach encompassing five stages: analysis, design, development, implementation, and evaluation. The sample consisted of 56 seventh-grade students from MTSN 2 Ponorogo.Findings- The research results show that data collection involved validity and reliability tests to ensure the instrument's effectiveness. Expert evaluations yielded an average validity score of 96%, categorizing the instrument as